Certain Results on Bicomplex Matrices (Global Journal of Science Frontier Research, 2018)
This paper begins the study of bicomplex matrices. In this paper, we have defined bicomplex matrices, determinant of a bicomplex square matrix and singular and non-singular matrices in C2. We have proved that the set of all bicomplex square matrices of order n is an algebra. We have given some definitions and results regarding adjoint and inverse of a matrix in C2. We have defined three types of conjugates and three types of tranjugates of a bicomplex matrix. With the help of these conjugates and tranjugates, we have also defined symmetric and skew - symmetric matrices, Hermitian and Skew - Hermitian matrices in C2.
Keywords: bicomplex matrices; conjugates matrices; tranjugate matrices; hermitian matrices; skew hermitian matrices